Attitudes toward driving after cannabis use: a systematic review - Bianca Boicu; Durr Al-Hakim; Yue Yuan; Jeffrey Brubacher (BMC, 2024)
Abstract Background Driving after cannabis use (DACU) is associated with increased risk of motor vehicle collisions. As cannabis legalization expands, DACU is emerging as a major public safety concern. Attitudes have a significant impact on behavioural decision making. As such, understanding the degree to which people have favorable or unfavorable evaluations of DACU is an important first step for informing prevention efforts. This systematic review summarizes existing evidence on attitudes toward DACU, their association with actual or intended DACU, and changes in attitudes following legalization of recreational cannabis. Methods Four electronic databases (MEDLINE, EMBASE, PsycINFO, and TRID) were searched for studies that reported attitudes or changes in attitudes toward DACU published between their inception dates and February 26 2024. A total of 1,099 records were retrieved. Studies were analyzed using an inductive thematic synthesis approach. Results Seventy studies from seven countries originating predominantly from the United States and Canada met inclusion criteria. Thematic analysis identified six themes. (I) Attitudes toward the safety and acceptability of DACU are mixed; participants in 35 studies predominantly expressed negative attitudes toward DACU (e.g., DACU is dangerous, affects driving ability, and increases crash risk). However, 20 studies reported opposing views. (II) Attitudes toward DACU vary by age, sex/gender, and cannabis use frequency; youth, men, and frequent cannabis users tended to view DACU more favorably than older participants, women, and occasional or non-users. (III) Attitudes toward DACU are associated with past DACU and intention to DACU. (IV) DACU is viewed more favorably than driving after drinking alcohol. (V) The relationship between legal status of recreational cannabis and attitudes toward DACU is unclear. (VI) Perceived risk of apprehension for DACU is low to moderate. Conclusions This review found that perceptions of DACU are primarily negative but mixed. Findings suggest that attitudes toward DACU are important targets for interventions to reduce this behaviour.